Prospección geológica de calizas en el sector Zambi, ubicado en la parroquia Zambi, cantón Catamayo, provincia de Loja. - Cobos Ramírez, Junior Alejandro (2024)
The purpose of this research work is the “Geological prospecting of limestone in the Zambi sector, which is located in the Zambi parish, Catamayo canton, Loja province”. It has a 40 hectares extension where the area of interest is delimited with a focus on the initial search for areas of calcium carbonate accumulation and determining the physical and chemical properties that these deposits has and analyzing their possible application for industrial activities. Once the bibliographic information has been obtained through office work, the first visit to the study area was made then the photographic survey was carried out by remote perception, which was used as a base to carry out the geological survey by describing outcrops and pits where three types of lithologies corresponding to limestone, clay and quartzite were evident. After having identified the rocks, samples were taken at different points in the study area and physical tests were carried out such as calculating specific weight, apparent weight and porosity; chemical tests corresponding to x-ray diffraction, x-ray fluorescence and carbonate purity. These analyzes determined the percentage of CaCo3 that exist in the limestones, thus compound being the most important with an average value of 77.56% CaCo3, classifying it as an impure marly limestone; likewise, elements such as Al₂O₃, SIO₂, P₂O₃, S, K₂O, CaO y Fe₂O₃ were identified, which according to their concentration percentages in the samples, allowed us to know the industrial use of limestone with the calculation of the hydraulic index, obtaining as a result that its use is for Portland cement. It is argued that this rock is directly related to the cement industry or construction industry. Key words: Geology, prospecting, limestone, industrial use.